Cellphone with Dial and Call Feature Design Prototype for Children with Autism Spectrum Disorder (ASD) - Bayu D. Wicaksono; Sritomo Wignjosoebroto (Jurnal Teknik ITS, 2012)
Autism Spectrum Disorder (ASD) is a term that used to explain neurological problems which affect mind, perception and concentration. The unfortunate condition of children with ASD lead more difficult to do long-distance communication, not only because of the lack of device that can be used exclusively by children with ASD (the physical as well as its interface), but also because of their general habits tends to destroy something in this case is a commercial cellphone. Identification of ASD children’s habit will be conducted by distributing questionnaires and interviews of the parties which are well acquainted with their daily activities such as parents and school teachers. To validate the questionnaire, has also been conducted ethnographic video capture. The design of cell phone’s prototype and dial & call software/application interface in it is done using the Quality Function Deployment (QFD) method as the results have been obtained from the collection of data on the habits of ASD children. In addition, there is also made a sound maker app.